Flowering Behaviour of Rice Varieties and its economic importance - Rautaray, S. K. (Indian Farming, 2015)
Rice is an unique crop having photoperiod sensitive, insensitive and weakly sensitive varieties. The degree of sensitivity also varies with varieties. Flowering behaviour of rice varieties is affected by thermo and photoperiod sensitivity and accordingly, optimum sowing date can be determined. If optimum sowing time is not adopted, situations like yield decrement to total crop failure may arise.